“School is not for me”: Young people’s perceptions of being a self-directed learner in a small rural Tasmanian town (Journal of Applied Learning and Teaching, 2022)
The Education Act (2016) was introduced in Tasmania to address the state’s high rates of early school leaving. Such legislative reforms may overlook informal factors that influence educational outcomes. In this paper we argue that a deeper understanding of the underlying drivers of retention and engagement in diverse social and cultural contexts is vital in supporting the Education Act. Drawing on qualitative data, this paper provides insights into how a group of Grade 10 students in a small rural town in Tasmania made the choice to leave school early or continue on to some form of post-compulsory education. Using Berger and Luckmann’s theory of sociology of everyday life together with Bourdieu’s (1990) concepts of social and cultural capital, this paper highlights how perceptions of being a self-directed learner and feelings about the future shaped the young people’s educational decisions. It emphasises how a localised form of social and cultural capital was associated with feelings of failure and anxiety about future learning, whereas a broader form of social and cultural capital was linked with more optimistic perceptions of being a self-directed learner. The paper suggests that the career aspirations, including university study, of young people living in regional areas may be supported through familiarisation with larger regional towns and raising their awareness of post school options.